Does social–behavioral adjustment mediate the relation between executive function and academic readiness? - Baptista, J.; Osório, A.; Martins, E. C.; Verissimo, M.; Martins, C. (Journal of Applied Developmental Psychology, 2016)
Research shows that executive function and social-behavioral adjustment during the preschool years are both associated with the successful acquisition of academic readiness abilities. However, studies bringing these constructs together in one investigation are lacking. This study addresses this gap by testing the extent to which social and behavioral adjustment mediated the association between executive function and academic readiness. Sixty-nine 63-76 month old children, enrolled in the last semester of the preschool year, participated in the present study. Tasks were administered to measure executive function and preacademic abilities, and teachers rated preschoolers' social-behavioral adjustment. Hierarchical regression analyses revealed that social-behavioral adaptation was a significant mediator of the effect of executive function on academic readiness, even after controlling for maternal education and child verbal ability. These findings extend prior research and suggest that executive function contributes to early academic achievement by influencing preschoolers' opportunities to be engaged in optimal social learning activities.